A density result in vector optimization - Alexander J. Zaslavski (International Journal of Mathematics and Mathematical Sciences)
We study a class of vector minimization problems on a complete metric space such that all its bounded closed subsets are compact. We show that a subclass of minimization problems with a nonclosed set of minimal values is dense in the whole class of minimization problems.